ORGANIC FARMING: FROM DEFINITIONS AND CONCEPTS TO THE AGRICULTURAL BUSINESS AND EVEN POLITICS - Indira Deniz ALIM; Aurel LUP (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This article tackles the issue of organic agriculture/farming in all its aspects, from origins to definitions, principles and characteristics, spatial development and world and national level. The older ecological movement is considered a precursor of organic farming that appeared as an agricultural system accompanied by the necessary regulations only in the last decades of the twentieth century. Opportunities are established in response to the anthropic aggression of any nature over the quality of the environment with direct influence on people’s health. The world consumer is ready to pay in this way for his/her health and life expectancy. In turn, the chronically sub-paid agricultural producer/farmer, with his work and efforts, sees organic farming as an opportunity to increase his income. Supported by the media, especially the press, organic farming is becoming more or less successful and an object of political choice.